Architecture in Anthropological Perspective: Structural Reflection on Local Architectural Dynamics - Gregorius Neonbasu; Reginaldo Christophori Lake; Pilipus Jeraman; Kolawole O. Morakinyo; Oluropo Stephen Ilesanmi (University of Merdeka Malang, 2024)
The objective of this study is to discuss the role of an anthropological perspective in architecture as well as structural reflection on the dynamics of architecture in relation to society. An anthropological lens can be used to study architecture as a manifestation of human culture in order to better understand the complex interactions between humans, the environment, and social structures. This research takes an anthropological approach to understanding architecture and investigates the dynamics of architecture as a cultural product influenced by social, technological, economic, and political changes. An analysis of the physical structure of architecture that reflects social structure, symbolism, and representation in architecture as a reflection of society is used to explain structural reflection. Case studies encompass vernacular, religious, colonial, and sustainable architecture. Understanding architecture from an anthropological standpoint allows humans to recognize the significance of cultural identity, the preservation of traditions, and their relationship with the physical environment as an art form in development.